Critical Care Handbook of the Massachusetts General Hospital. - Wiener-Kronish, Jeanine P. (Wolters Kluwer Health, 2015)
"Now reflecting a greater focus on today's multidisciplinary approach to care, Critical Care Handbook of the Massachusetts General Hospital, 6th Edition, remains your go-to guide for practical, complete, and current information on medical and surgical critical care. The user-friendly, outline format is designed for rapid reference, providing reliable, hospital-tested protocols that reflect today's most advanced critical care practices. Key Features Heavily revised to reflect today's need to include all care providers to optimize treatment New section on Health Care Services, with chapters on handovers and transitions, long-term outcomes of ICU patients, EICU and electronic systems, quality improvement, and more New chapters on critical care management of Ebola virus disease, ECMO and ventricular assist devices, and critical care of the obstetrical patient New videos available online Complete, concise, full-color coverage of this rapidly enlarging field Convenient pocket size for on-the-go reference Now with the print edition, enjoy the bundled interactive eBook edition, which can be downloaded to your tablet and smartphone or accessed online and includes features like: Complete content with enhanced navigation Powerful search tools and smart navigation cross-links that pull results from content in the book, your notes, and even the web Cross-linked pages, references, and more for easy navigation Highlighting tool for easier reference of key content throughout the text Ability to take and share notes with friends and colleagues Quick reference tabbing to save your favorite content for future use"--